Fenomena Strawberry Generation dan Relevansinya dalam Perspektif Kitab Syarh Nahju al-Balaghah: The Strawberry Generation Phenomenon and Its Relevance in the Perspective of Syarh Nahju al-Balaghah - Shafira, Elsa Balqis (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This research discusses about the Strawberry Generation, which possesses potential and challenges in the development of civilization. The term